2017
DOI: 10.1017/s1368980017001744
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the validity of commercial and municipal food environment data sets in Vancouver, Canada

Abstract: Objective: The present study assessed systematic bias and the effects of data set error on the validity of food environment measures in two municipal and two commercial secondary data sets. Design: Sensitivity, positive predictive value (PPV) and concordance were calculated by comparing two municipal and two commercial secondary data sets with ground-truthed data collected within 800 m buffers surrounding twenty-six schools. Logistic regression examined associations of sensitivity and PPV with commercial densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…In this sense, we found fewer differences between area-level socioeconomic status, population density and the proportion of outlets that were correctly matched in the secondary data by using location (liberal) matching. These findings are in line with previous research, which also reported no differences by area-level deprivation [13,45,48,54,55]. Yet, we found some evidence for a systematic bias when applying a stricter matching strategy.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this sense, we found fewer differences between area-level socioeconomic status, population density and the proportion of outlets that were correctly matched in the secondary data by using location (liberal) matching. These findings are in line with previous research, which also reported no differences by area-level deprivation [13,45,48,54,55]. Yet, we found some evidence for a systematic bias when applying a stricter matching strategy.…”
Section: Discussionsupporting
confidence: 93%
“…While this idea has been suggested by previous studies [47,48], our study extends previous research because we examined the validity of secondary data sources in a European context and included multiple types of food outlets (e.g., specialized food retailers) [49,50]. This is important, because previous studies have found that independent (non-chain) food outlets are more likely to be missed in commercial datasets [31,32,33,51].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We also excluded food retail outlets inside institutions (e.g. schools and universities) because they are not freely available to the general public and so do not constitute part of the community food environment, but rather the organizational food environment [3,11].…”
Section: Google Earth Data Acquisitionmentioning
confidence: 99%